PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA PADANGSIDIMPUAN: ANALISIS PARTISIPASI POLITIK GENERASI MUDA - Gunawan, Rasyd; Nasution, Hasyimsyah (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the political participation of young people in the 2024 Padangsidempuan mayoral and deputy mayoral elections. Youth participation is a crucial issue given the dominance of young voters in the current political demographic. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the youth in Padangsidempuan are increasingly active in following political processes, particularly through involvement in campaigns, public discussions, and evaluating the visions and missions of regional head candidates. Social media serves as the main channel facilitating their involvement. However, challenges still exist, including political apathy among some young people and the lack of ongoing political education. Therefore, collaboration between educational institutions, election organizers, and local communities is essential to encourage more substantial and quality political participation.